Pelatihan Pemanfaatan Artificial Intelijen (Ai) Dalam Pembuatan Konten Kreatif Di SMPN 17 Kota Bengkulu - Yansyah, Novi; Savela, Yela; Widiatama, Danang; Afriandi, Afriandi; Jusiati, Arini; Octaviani, Vethy; Maryaningsih, Maryaningsih; Narti, Sri (Jurnal Gotong Royong, 2025)
This study investigates the utilization of Artificial Intelligence (AI) in content creation among students at SMPN 17 Bengkulu City. Recognizing the growing significance of AI in our daily lives, the study aims to address the limited awareness and application of AI tools among these students. The research focuses on introducing AI concepts and providing practical training to students on leveraging AI for creative content development. The findings reveal a positive impact, with students demonstrating increased understanding, enthusiasm, and a newfound ability to utilize AI effectively in their digital creative endeavors.